Nutrition Webinars for Students and Health Professionals: Indonesian Study During Covid-19 Pandemic - Wisnuwardani, Ratih Wirapuspita; Afiah, Nurul; Noviasty, Reny; Faisal, Muhammad; Kurniawati, Eva R (Jurnal Kesehatan Masyarakat, 2024)
Recently, there has been an increase in obesity cases among adolescents in Indonesia with a prevalence rate of 19%, which exceeds the national prevalence of 16%. This was caused by the decrease in physical activities and consumption of fruit and vegetables by 95% of the population during the COVID-19 pandemic. This study aimed to foster the development of a Nutrition Education Center (Nutrecent) as a distance learning to promote the consumption of plant-based foods containing polyphenols such as vegetables and fruits. This was a quasi-experiment with three Nutrecent (Nutrition Education Centre) Webinar series and an international webinar. Participants were high school and college students, health workers, and the general public. A total of 654 participants were included in the analysis. The statistical results showed no significant improvement in knowledge due to the Nutrecent webinar series activities, but there was a significant improvement due to the international webinar (p-value 0.001). Online learning is only effective for students and adults with previous knowledge of the webinar topic. Consequently, there is a need to include the importance of consuming plant-based foods in the school curriculum.